Overexpression of IbFAD8 Enhances the Low-Temperature Storage Ability and Alpha-Linolenic Acid Content of Sweetpotato Tuberous Roots - Lee, Chan-Ju; Kim, So-Eun; Park, Sul-U; Lim, Ye-Hoon; Ji, Chang Yoon; Jo, Hyun; Lee, Jeong-Dong; Yoon, Ung-Han; Kim, Ho Soo; Kwak, Sang-Soo (Frontiers in Plant Science, 2021)
Sweetpotato is an emerging food crop that ensures food and nutrition security in the face of climate change. Alpha-linoleic acid (ALA) is one of the key factors affecting plant stress tolerance and is also an essential nutrient in humans. In plants, fatty acid desaturase 8 (FAD8) synthesizes ALA from linoleic acid (LA). Previously, we identified the cold-induced IbFAD8 gene from RNA-seq of sweetpotato tuberous roots stored at low-temperature. In this study, we investigated the effect of IbFAD8 on the low-temperature storage ability and ALA content of the tuberous roots of sweetpotato. Transgenic sweetpotato plants overexpressing IbFAD8 (TF plants) exhibited increased cold and drought stress tolerance and enhanced heat stress susceptibility compared with non-transgenic (NT) plants. The ALA content of the tuberous roots of TF plants (0.19 g/100 g DW) was ca. 3.8-fold higher than that of NT plants (0.05 g/100 g DW), resulting in 8–9-fold increase in the ALA/LA ratio in TF plants. Furthermore, tuberous roots of TF plants showed better low-temperature storage ability compared with NT plants. These results indicate that IbFAD8 is a valuable candidate gene for increasing the ALA content, environmental stress tolerance, and low-temperature storage ability of sweetpotato tuberous roots via molecular breeding.